Validation and field evaluation of a competitive enzyme-linked immunosorbent assay for diagnosis of Babesia bovis infections in Argentina - Dominguez, Mariana Gabriela (2012)
Infections by Babesia bovis limit cattle production and cause important economic losses in tropical and subtropical areas around the world. Monitoring of calf sera can be used to detect unprotected cattle herds and to decide on strategic control measures, as well as for epidemiological studies. Merozoite surface antigen 2c (MSA-2c) is an immunodominant surface protein expressed in B. bovis merozoites and sporozoites and contains B-cell epitopes that are conserved among geographic isolates. A monoclonal antibody against recombinant MSA-2c (rMSA-2c) was previously shown to inhibit the binding of anti-B. bovis antibodies to a parasite B-cell epitope in a competitive enzyme-linked immunosorbent assay (cELISA) format. In the work at hand, the parameters of this cELISA were reevaluated and adjusted when necessary, and a cutoff value was determined by receiver operator characteristic (ROC) curve analysis of a total of 357 bovine sera of known reactivity, as assessed by indirect immunofluorescence assay (IFAT). The established rMSA-2c cELISA demonstrated a specificity of 98% and a sensitivity of 96.2%. An additional set of 303 field bovine sera from regions where ticks are endemic and tick-free regions of Argentina was tested by both rMSA-2c cELISA and IFAT, and the results were shown to be in very good agreement (kappa index, 0.8325). The performance shown by rMSA-2c cELISA in the detection of B. bovis-specific antibodies and its suitability for standardization and large-scale production, as well as the possibility of its application in most veterinary diagnostic laboratories, make the assay a powerful tool for the surveillance of herd immunity as a strategic measure for the control of bovine babesiosis.